Research on Green Recycling Technology of Key Metals in Waste Lithium-ion Batteries - Jiang Juncheng (MATEC Web of Conferences)
Owing to the scarcity of critical metal resources such as lithium and cobalt, as well as the urgent need for environmental protection, the efficient regeneration of cathode materials for lithium-ion batteries (LIBs) has become a core issue in supporting the sustainable development of the electric vehicle industry. At present, the industrial sector mainly relies on pyrometallurgy and hydrometallurgy technologies to recover metals, but the former is limited by high energy consumption and greenhouse gas emissions, while the latter faces the challenges of chemical contamination and high cost. Therefore, there is an urgent need to develop green and economical alternative technologies to avoid the environmental risks caused by landfills of used batteries and achieve resource circulation. In this study, the feasibility of emerging processes such as bio-metallurgy (microbial leaching), eutectic solvents (DES), and direct regeneration was systematically evaluated. Based on this, it is proposed to optimize process efficiency by integrating multiple technologies (such as microwave-assisted enhanced reaction and biomass co-reduction), and promote policy guidance and standardized design, to accelerate the transformation of the LIB industry to a circular economy and contribute to the global carbon neutrality goal and sustainable resource management.